Comment on CdTe solar cell efficiency - Alexander P. Kirk (Journal of Alloys and Metallurgical Systems, 2024)
Based on computer simulations, it has been reported in October 2023 that conventional cadmium telluride (CdTe) solar cells can achieve actual air mass 1.5 global (AM 1.5 G) power conversion efficiency up to 35.79% [R. Hosen et al., Journal of Alloys and Metallurgical Systems 4 (2023) 100041]. Since the ideal Shockley-Queisser detailed balance-limiting power conversion efficiency of a 1.5 eV CdTe solar cell is only 32.1% at 25 °C, it is unlikely that an actual, conventional, CdTe solar cell will exceed this efficiency.